Simultaneous determination of metolazone and valsartan in plasma by on-line SPE coupled with liquid chromatography/tandem mass spectrometry. Issue 5 (October 2017) - Zhou, Jiezhao; Chen, Meiling; Li, Ying; Yu, Fanglin; Cheng, Xiaohui; Yang, Yang; Liu, Yan; Xie, Xiangyang; Li, Zhiping; Zhang, Hui; Mei, Xingguo
Combination of metolazone (0.5 mg) and valsartan (80 mg) has been verified as a promising therapy treatment for hypertension. In order to facilitate to pharmacokinetic research, it needs a method for the simultaneously determination of metolazone and valsartan in biological samples. However, there are no relative reports so far. In order to facilitate to pharmacokinetic research, an on-line solid phase extraction coupled with liquid chromatography-tandem mass spectrometry method for the simultaneous determination of metolazone and valsartan in beagle dog plasma was developed and validated in this study. An on-line solid phase extraction column Retain PEP Javelin (10 mm × 2.1 mm) was used to remove impurities in plasma samples. The metolazone, valsartan and internal standard (losartan) were separated on a Poroshell 120 SB-C18 column (4.6 mm × 50 mm × 2.7 µm) with a gradient elution procedure. Acidified acetonitrile/water mixture was used as a mobile phase. The selected multiple-reaction monitoring mode in positive ion was performed and the parent to the product transitions m/z 366/259, m/z 436.2/291 and m/z 423.4/207 were used to measure the metolazone, valsartan and losartan. The method was linear over the range of 0.1–100 ng/mL and 1–1000 ng/mL for metolazone and valsartan, respectively. This method was validated in terms of specificity, linearity, sensitivity, precision, accuracy, matrix effect, and stability and then successfully applied to pharmacokinetic studies of the metolazone and valsartan combination tablets in beagle dogs.